Continuous deep sedation until death – what is it and why its built controversy? - Tomczyk, Martyna; Sopata, Maciej Jarosław; Viallard, Marcel-Louis; Beloucif, Sadek; Hervé, Christian (Medycyna Paliatywna/Palliative Medicine, 2015)
In this article authors described a special kind of sedation – continuous deep sedation until death of the patient. They present terminological semantic problems that are present with this procedure, its frequency of use, medical indications and ethical dilemmas. Authors also describe the potential determinants of its controversial use. The main factor explaining these results is the social-cultural influence of the studied country. Medical, social and juridical situation in Poland has been described and discussed.